2014
DOI: 10.5614/j.math.fund.sci.2014.46.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and NMR analysis of Curcuma xanthorrhiza extract and fractions

Abstract: Abstract. An acetone extract of Curcuma xanthorrhiza rhizomes and the nhexane and chloroform fractions obtained from it were tested on eight pathogenic bacteria. The results showed that the acetone extract and the nhexane fraction exhibited significant activities against Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus aureus, and weak activities against Shigella dysenteriae and Vibrio cholerae. They were inactive against Escherichia coli, Enterobacter aerogenes and Salmonella thypi, while the chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The extract showed inactive against Escherichia coli, Enterobacter aerogenes and Salmonella thypi, while the chloroform fraction was devoid of activities (Diastuti, Syah, Juliawaty, & Singgih, 2014). Xanthorrhizol isolated from the ethanol extract of Curcuma xanthorrhiza is a sesquiterpene compound showed strongly antibacterial activity with thermal and pH stability (Lee, Shim, Rukayadi, & Hwang, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The extract showed inactive against Escherichia coli, Enterobacter aerogenes and Salmonella thypi, while the chloroform fraction was devoid of activities (Diastuti, Syah, Juliawaty, & Singgih, 2014). Xanthorrhizol isolated from the ethanol extract of Curcuma xanthorrhiza is a sesquiterpene compound showed strongly antibacterial activity with thermal and pH stability (Lee, Shim, Rukayadi, & Hwang, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance levels are rising, therefore the search for novel bactericidal agents has increased over the past years. A main focus is using medicinal herbs that are widely available, have fewer side effects and have excellent antimicrobial potential [28]. Hence, the investigation of substitute medicines from plants that are active against multi-resistant pathogenic bacteria has increased all around the globe [29].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that a high concentration of the extract was needed to inhibit and kill the P. aeruginosa culture (200 and 800 mg/mL, respectively). In the study done by Diastuti et al 50 , the MIC and MBC values of the C. xanthorrhiza Roxb. extracts on the P. aeruginosa were much lower than in this study.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) and mentioning
confidence: 99%